1976
DOI: 10.1002/aic.690220104
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of models for fluidized bed catalytic reactors

Abstract: The countercurrent backmixing model of a fluidized bed reactor predicts axial concentration profiles quite different from those suggested by simple two‐phase models. The models can also be distinguished in terms of the dependence of conversion on operating variables.An experimental study of ozone decomposition in a reactor of 22.9 cm diameter has provided extensive data for comparison with backmixing and two‐phase models which incorporate bubble size variation. The measured profiles show a minimum concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 6 publications
3
66
0
Order By: Relevance
“…The ozone enters the bed at 1.5 cm from the bottom, while Barracuda calculations have ozone entering at the bottom. As noted by Fryer and Potter (1976) this gives an effectively shorter ozone decomposition zone. A 11.5 cm deep bed has a 13% smaller effective reaction zone.…”
Section: Fluidized Bed Ozone Decompositionmentioning
confidence: 90%
See 3 more Smart Citations
“…The ozone enters the bed at 1.5 cm from the bottom, while Barracuda calculations have ozone entering at the bottom. As noted by Fryer and Potter (1976) this gives an effectively shorter ozone decomposition zone. A 11.5 cm deep bed has a 13% smaller effective reaction zone.…”
Section: Fluidized Bed Ozone Decompositionmentioning
confidence: 90%
“…10. The measured minimum fluidization velocity (U mf ) was 1.7 cm/s (Fryer and Potter, 1976), and from Fig. 10, the calculated U mf is approximately 1.6 cm/s.…”
Section: Fluidized Bed Ozone Decompositionmentioning
confidence: 97%
See 2 more Smart Citations
“…Such measurement has been believed to be highly biased, and, more importantly, no standard errors or deviations of data have been reported [8]. Fryer and Potter [9] reported that the experimental technique might well underestimate the bed expansion due to the diffusing characteristic of the bed surface. The other frequently employed method is to plot the time-mean gauge pressure (single-point pressure) against the height of the pressure transducer taps, where the intersection of the two slopes corresponds to the height of the expanded bed.…”
Section: Bed Expansionmentioning
confidence: 99%